Extensive pneumocephalus in a fatal central nervous system infection caused by NDM-1–producing carbapenem-resistant Klebsiella pneumoniae: a case report - Chen Zhang; Ye Lu; Jun Ni; Lina Chen; Qi Li; Fangyu Yu; Xiaohong Zhou (Frontiers in Medicine, 2026)
Background Central nervous system (CNS) infections caused by New Delhi metallo-β-lactamase-1 (NDM-1)-producing carbapenem-resistant Klebsiella pneumoniae (CRKP) are rare but associated with extremely high mortality because of extensive antimicrobial resistance and poor blood–brain barrier (BBB) penetration. To the best of our knowledge, there have been no published reports of pneumocephalus associated with infection caused by NDM-1-producing K. pneumoniae . Case presentation We report an 18-year-old woman who developed bloodstream infection and metastatic CNS infection following severe thoracoabdominal crush injury. Serial cerebrospinal fluid (CSF) cultures repeatedly yielded NDM-1-producing CRKP despite multiple adjustments of antimicrobial therapy. Retrospective whole-genome sequencing demonstrated that blood and CSF isolates belonged to the same clonal lineage carrying the bla NDM-1 gene on an IncX3 plasmid, confirming hematogenous dissemination. Serial cranial computed tomography revealed progressive diffuse cerebral edema and extensive pneumocephalus in the absence of skull fracture or neurosurgical intervention. Persistent microbiological failure was mainly attributed to the combination of NDM-1-mediated multidrug resistance and inadequate CNS antibiotic exposure, which ultimately led to the patient’s death. Conclusion This case illustrates the devastating clinical course of NDM-1-producing CRKP CNS infection and identifies extensive pneumocephalus as a rare but potentially fatal complication. It emphasizes the importance of early molecular diagnosis, repeated CSF microbiological assessment, optimization of antimicrobial regimens with adequate CNS penetration, and implementation of effective infection-control strategies. The case also highlights the urgent need for novel therapeutic approaches against metallo-β-lactamase-producing pathogens.